2017
DOI: 10.1002/cb.1654
|View full text |Cite
|
Sign up to set email alerts
|

Safe driving communication: A regulatory focus perspective

Abstract: This research article examines the effects of self‐regulation on adolescents' aggressive driving tendencies and their attitudes toward safe driving communication. Two experimental studies demonstrate that an individual's regulatory orientation is a good predictor of aggressive driving tendencies and that self‐regulation plays a moderating role on the effects of safe driving messages on recipients' attitudes. Specifically, the findings reveal that promotion‐oriented (vs. prevention‐oriented) individuals are mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 87 publications
(161 reference statements)
1
6
0
Order By: Relevance
“…Building on literature relating regulatory focus to traffic-related risk attitudes (Craciun et al, 2017 ), our results also specify boundary conditions for this effect, in that the effect is mitigated for consumers strongly occupied by regulatory promotion or prevention tendencies. Importantly, the results of study 2 suggest the potential for broad behavioural effects and corroborate effects of safety cues on generalized risk taking reported in literature earlier.…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…Building on literature relating regulatory focus to traffic-related risk attitudes (Craciun et al, 2017 ), our results also specify boundary conditions for this effect, in that the effect is mitigated for consumers strongly occupied by regulatory promotion or prevention tendencies. Importantly, the results of study 2 suggest the potential for broad behavioural effects and corroborate effects of safety cues on generalized risk taking reported in literature earlier.…”
Section: Discussionsupporting
confidence: 51%
“…Therefore, regulatory focus is measured as two separate subscales of promotion and prevention focus. Literature shows that these tendencies affect risk attitudes in traffic (Craciun et al, 2017 ). We propose that strong regulatory predispositions—either promotion or prevention—reduce consumers’ sensitivity to context effects.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Generally, customers who reported a negative consumption experience tend to be pessimistic, as a bad experience leads to negative emotions, prevention focus and sensitivity to punishment ( Johnson and Chang, 2008). Prevention-focused customers who had a negative consumption experience want to express their rage, frustration and annoyance in eWOM communication to hit back at the culprit company (Craciun et al, 2017;Shin et al, 2014). Another study found that injustice or negative consumption experience leads to the expression of negative feelings and the use of emotional language in eWOM messages (Yap et al, 2013) and triggers lower purchase intention (Hsu et al, 2017).…”
Section: Vengeancementioning
confidence: 99%
“…The match between a person's regulatory focus and resulting behaviors and strategies is called “regulatory fit” (Motyka et al, 2014; Praxmarer‐Carus et al, 2022; Wang et al, 2021). Promotion‐focused people seek the easiest and most efficient solutions to accomplish goals and once difficulties arise, they usually try something new (Craciun et al, 2017; Crowe & Higgins, 1997; Higgins, 2000). Prevention‐focused people take minimum risks, seek to avoid negative outcomes, and remain vigilant in trying new approaches (Kees et al, 2010).…”
Section: Conceptual Frameworkmentioning
confidence: 99%